1996
DOI: 10.1016/0006-2952(95)02194-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytochrome P450 induction on the metabolism and toxicity of ochratoxin A

Abstract: The role of cytochrome P-450 in me stimulation of lipid peroxidation induccd by thc mycotoxin ochratoxin A (OTA) has been investigated. Purified cytochrome P-450 (liB I) could effectively replace EDTA in stimulating lipid pefOxidation in a reconstituted system l'Onsisling of phospholipid vesicles, NADPH-cYlochrome P-450rcduc!ase, FeJ+, EDTA and NADPll, suggesting that it could mediate the transfer of electrons from NADPH to foc3,. Microsomcs isolated from liven of cobalt protoporphyrin IX-treated rllts (in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 66 publications
4
25
0
1
Order By: Relevance
“…Their formation was dependent on the type of cells and the PB pretreatment. In this study, we confirm the increase of 4-[R]-OH-OTA and 10-OH-OTA after PB pretreatment observed by others [Størmer and Pederson, 1980;Hietanen et al, 1986Hietanen et al, , 1991Omar et al, 1996]. Little is known about the genotoxicity of these metabolites.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Their formation was dependent on the type of cells and the PB pretreatment. In this study, we confirm the increase of 4-[R]-OH-OTA and 10-OH-OTA after PB pretreatment observed by others [Størmer and Pederson, 1980;Hietanen et al, 1986Hietanen et al, , 1991Omar et al, 1996]. Little is known about the genotoxicity of these metabolites.…”
Section: Discussionsupporting
confidence: 94%
“…Before this investigation, the metabolism of OTA has been studied both in vitro and in vivo mostly in liver (for a review, see Størmer, 1992) but also in kidney [Hietanen et al, 1986;Pfohl-Leszkowicz et al, 1993b]. The main metabolites formed were hydroxylated compounds: 4-[R]-and 4-[S]-hydroxy-OTA (4-[R]-and 4-[S]-OH-OTA) in rats and also10-hydroxy-OTA (10-OH-OTA) in rabbits [Størmer et al, 1983], which could be formed by CYP 1A1/2, 2B1, 3A1/2, and also by peroxydasic pathways in bronchial and kidney cells [Ueno,1985;Størmer, 1992;Grosse et al, 1995;Omar et al, 1996;Grosse et al, 1997;Pinelli et al, 1999]. The formation of these OTA derivatives was induced by phenobarbital (PB) [Størmer and Pederson, 1980;Hietanen et al, 1986Hietanen et al, , 1991Omar et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…The IARC has classified OTA as a "possible human carcinogen (Group 2B)" based on sufficient evidence for carcinogenicity in experimental animal studies and inadequate evidence in humans (IARC, 1993). The toxic-kinetic parameters of OTA have not been well established in humans, but OTA showed high availability after oral administration in some animal studies (Fuchs and Hult, 1992;Omar et al, 1996).…”
mentioning
confidence: 99%
“…OTA produces an inhibition of protein synthesis and lipid peroxidation by oxidative processes (Gautier et al, 2001;Omar et al, 1996).…”
mentioning
confidence: 99%
“…Results from studies of P-450 induction in rat liver microsomes showed that the P-450 isoforms IA1/IA2, IIB1, and IIIA1/IIIA2 are involved in the formation of the (4R)-4-hydroxyochratoxin-A metabolite of OA and, to a lesser extent, (4S)-4-hydroxyochratoxin-A (Omar et al, 1996). Results also indicated that P-450IIB1-dependent mixed-function oxidation to OA leads to its detoxification (Omar et al, 1996).…”
Section: Toxicokinetics and Metabolismmentioning
confidence: 94%